MOTIVASI DAN KOMPENSASI KERJA YANG MEMPENGARUHI KINERJA KARYAWAN DI PT. FEDERAL INTERNASIONAL FINANCE (FIF) CABANG CIKANDE - Fuadi Fuadi; Sari Putri Pertiwi (Jurnal Valuasi: Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2023)
This research was conducted to determine the effect of work motivation and compensation on employee performance at the Federal International Finance (FIF) Cikande Branch, Serang Regency, using data collection techniques through questionnaires, the sample being 52 people who were employees of the Federal International Finance (FIF) Cikande Branch, Serang Regency. The analytical method used is descriptive analysis method, statistical analysis method consisting of partial significance testing (t-test) and F-test, as well as testing the coefficient of determination. Based on the results of the descriptive analysis, it shows that motivation and employee performance are good because there are intervals (3.41-4.20), while work compensation is very good because there are intervals (4.20-5.00). In partial test, there is an influence between brand image and price on consumer loyalty. From the results of the F test, the value of Fcount (62.490) > Ftable (3.183), then H0 is rejected and Ha is accepted, meaning that there is a joint positive and significant influence between work motivation and compensation on the performance of employees of PT. Federal International Finance (FIF) Cikande Branch. From the multiple correlation value of 0.848 which indicates a very strong relationship between work motivation and compensation on employee performance. The coefficient of determination value of 0.718 indicates the level of contribution of brand image and price variables to loyalty of 71.8%, while the remaining 28.2% is influenced by other variables outside the model equation